The impact of drug and narcotic use on middle and secondary school students in Al-Hay District ,Wasit Education - Ass.Lect Hamid Shamkhi qaed Al- Atabi (Journal of College of Education, 2025)
The study aimed to identify the phenomenon of drug abuse in Iraq among a sample of middle and secondary school students in the Al-Hayy District, Wasit Education. The researcher used the descriptive and analytical approach. The study population consisted of all middle and secondary school students in the Al-Hayy District, Wasit Education, totaling (11,750) male and female students. The study was conducted on a sample of (80) male and female students. The researcher randomly selected the research sample from males and females from the middle and secondary schools. The research study used the Drug Abuse Scale among Secondary School Students. The results of the statistical analysis of the data showed that their average score was (21.78) with a standard deviation of (3.04). When comparing the calculated t-value (4.56) with the tabular value of (1.99) at a significance level of (0.05), the researcher came up with a set of recommendations and proposals
Keywords: drugs, narcotics, school students , Wasit Education